Dual Energy Computed Tomography and Contrast Dose. Issue 4 (5th December 2021) - Corrias, Giuseppe; Mahmood, Usman; Pizzi, Aldo; Sawan, Peter; Saba, Luca; Spinato, Giacomo; Mondanelli, Nicola; Mannelli, Lorenzo
Despite the great diagnostic improvements that CT has introduced, which have allowed it to spread widely and become one of the most important tools in medical imaging, this technique has always had to face two main inconveniences: the iodinated contrast media with its known adverse reactions and the exposure to ionizing radiation. The evaluation of patient safety is a fundamental parameter for the introduction of any new technology in clinical practice. In recent years, clinical applications of Dual Energy Computed Tomography (DECT) continue to grow, such as in its molecular characterization capacity, which has introduced a new method to study pathological tissues. Furthermore, numerous studies have shown that with the use of this innovative technique, it is also possible to reduce both the contrast medium load and the ionizing radiation dose compared to conventional CT standard protocols. The purpose of our review is to highlight how technological advances, new contrast media administration techniques such as the split bolus, and DECT capabilities of reconstructing virtual monochromatic images and virtual non-enhanced images reduce the risks of CT examinations, thus improving the risk-benefit ratio for patients. We will first examine the basics of contrast agent adverse reactions, the interaction of ionizing radiation, and DECT physical principles, and then we review those studies that show the potential benefits of DECT.